Time and causility: A Monte Carlo assessment of the timing-of-events approach - Simen Gaure; Knut Røed; Tao Zhang (University of Oslo, Department of Economics, 2005)
We present new Monte Carlo evidence regarding the feasibility of separating causality from selection within non-experimental interval-censored duration data, by means of the nonparametric maximum likelihood estimator (NPMLE). Key findings are: i) the NPMLE is extremely reliable, and it accurately separates the causal effects of treatment and duration dependence from sorting effects, almost regardless of the true unobserved heterogeneity distribution; ii) the NPMLE is normally distributed, and standard errors can be computed directly from the optimally selected model; and iii)unjustified restrictions on the heterogeneity distribution, e.g., in terms of a prespecified number of support points, may cause substantial bias.
Keywords: C14; C15; C41; 330; NPMLE; treatment effect; Monte-Carlo-Methode; Schätztheorie; Maximum-Likelihood-Methode